Cryo-EM structure of nucleotide-bound Tel1ATM unravels the molecular basis of inhibition and structural rationale for disease-associated mutations - Yates,L; Williams,R; Hailemariam,S; Ayala,R; Zhang,X (Structure, 2020)
Yeast Tel1 and its highly conserved human orthologue ATM are large protein kinases centralto the maintenance of genome integrity. Mutations in ATM are found in ataxia-telangiectasia(A-T) patients and ATM is one of the most frequently mutated genes in many cancers. Usingcryo electron microscopy, we present the structure of Tel1 in a nucleotide-bound state. Ourstructure reveals molecular details of key residues surrounding the nucleotide binding site andprovides a structural and molecular basis for its intrinsically low basal activity. We show thatthe catalytic residues are in a productive conformation for catalysis, but the PIKK-regulatorydomain-Insert (PRD-I) restricts peptide-substrate access and the N-lobe is in an openconformation, thus explaining the requirement for Tel1 activation. Structural comparisons withother PIKKs suggest a conserved and common allosteric activation mechanism. Our work alsoprovides a structural rationale for many mutations found in A-T and cancer.